Impact of a music therapy program on mental health and school attendance among female adolescents in Kasai-Central province, Democratic Republic of Congo - Lisa Zook; Ali Bitenga Alexandre; Michelle M. Hood; Sioban D. Harlow (Cambridge Prisms: Global Mental Health)
This study assessed whether a music therapy program improved mental health and school attendance among girls in the Democratic Republic of Congo (DRC) following economic and conflict-related insecurity. It included 483 girls aged 10–14 who participated in the Healing in Harmony (HiH) program, implemented by World Vision and Make Music Matter in Kasai-Central province. Participants completed surveys before and after the program, and up to two follow-up interviews assessing depression, anxiety, self-esteem, and school attendance. Before the program, 36.0% (95% CI 31.7%–40.3%) and 60.5% (95% CI 56.1%–64.8%) screened positive for depression and anxiety, respectively. After participation, the risk of screening positive declined by 75% for depression (RR = 0.27, 95% CI 0.22–0.32) and by about half for anxiety (RR = 0.46, 95% CI 0.41–0.53), with improvements sustained up to 17 months. Self-esteem scores increased by 3.93 points (95% CI 3.22–4.64, p<0.001). School absenteeism decreased from 10% (95% CI 7.2%–12.6%) to 5.4% (RR = 0.54, 95% CI 0.40–0.73). Participation in HiH was associated with sustained improvements in mental health and school attendance. These findings support integrating psychosocial care into humanitarian responses to improve both mental health and educational outcomes for crisis-affected children.